2015
DOI: 10.1371/journal.pone.0118067
|View full text |Cite
|
Sign up to set email alerts
|

Per-Oral Immunization with Antigen-Conjugated Nanoparticles followed by Sub-Cutaneous Boosting Immunization Induces Long-Lasting Mucosal and Systemic Antibody Responses in Mice

Abstract: Food or water-borne enteric pathogens invade their hosts via intestinal mucosal surfaces, thus developing effective oral vaccines would greatly reduce the burden of infectious diseases. The nature of the antigen, as well as the mode of its internalization in the intestinal mucosa affects the ensuing immune response. We show that model protein antigen ovalbumin (Ova) given per-orally (p.o.) induces oral tolerance (OT), characterized by systemic IgG1—dominated antibody response, which cannot be boosted by sub-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(46 citation statements)
references
References 58 publications
3
43
0
Order By: Relevance
“…priming and p.o. boosting immunization . These findings highlight the fact that in addition to the NP size, antigen administration route and prime‐boost immunization strategy are critical determinants of NP immunogenicity.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…priming and p.o. boosting immunization . These findings highlight the fact that in addition to the NP size, antigen administration route and prime‐boost immunization strategy are critical determinants of NP immunogenicity.…”
Section: Introductionmentioning
confidence: 83%
“…NPs larger than 200 nm have been mostly used for antigen and drug delivery because they can carry a large amount of cargo. In regard to antigen delivery, studies showing superior immunogenicity of both large and small NPs have been published, however, due to the varying properties of NPs used in these studies (such as NP chemistry, charge, antigen encapsulation, NP rigidity, and so forth), it is difficult to draw a definitive conclusion that NP size alone determines their immunogenicity. Moreover, NPs have been used in various prime‐boost immunization schemes, and are administered with (or without) adjuvants, thus additionally affecting their immunogenicity and making comparisons between studies even more challenging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Howe et al [70] recently demonstrated that while high doses of soluble OVA administered orally induced oral tolerance, OVA-coated nanoparticles (NP-OVA) induced systemic IgG1/IgG2c as well as high-affinity sIgA responses. These responses were boosted by subcutaneous injections of OVA + CFA or oral NP-OVA.…”
Section: The Tendency Of Antigen To Enter the Galt: Importance Of Beimentioning
confidence: 99%